An analysis of determinants of the adoption of Mobile Health (mHealth) - Miguel Martins, Nayra Leandro (2021)
Given the increasing use of the Internet and mobile technologies, this study is pertinent as it seeks to analyze the factorsthat determine the adoption of Mobile Health (mHealth). To that end, the proposed conceptual model integrates the UnifiedTheory of Acceptance and Use of Technology (UTAUT2), Perceived Health Condition, eHealth Literacy and Perceived HealthCompetence as determinants of the adoption of mHealth. To answer the research questions, we used an online questionnaireadministered to a non-probabilistic sample of Brazilian and Portuguese individuals who have or have not used mHealth. Datawere analyzed using SPSS and SmartPLS3 software. The results indicate that adoption of mHealth is heavily impacted only bysome UTAUT2 variables. The 'Performance Expectancy' dimension was found to heavily impact the adoption of mHealth amongboth users and non-users.